THE SOCIAL COST OF CARBON SHOULD NOT BE USED FOR MAKINGENERGY POLICY DECISIONS - LESSER, JONATHAN (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2025)
This paper argues that the social cost of carbon (SCC) should not be used to determine energy policies. The SCC, which is supposed to represent the avoided cost of greenhouse gas emissions, has been used to justify state and federal energy policy decisions, such as offshore wind procurements and the U.S. Environmental Protection Agency’s vehicle emissions standards. This paper argues that SCC values should not be used, not because climate change is not real, but because the approaches used to estimate SCC values, primarily through integrated assessment models (IAMs) but also using expert opinions, are based on layers of arbitrary and unverifiable assumptions. The reasons why include: (i) the hubris of believing it is possible to develop accurate forecasts regarding technological developments 300 to 1,000 years into the future; (ii) the fundamental uncertainties underlying SCC estimates, such as defining the pre-industrial time period and measuring world temperatures during that period; (iii) the inherent arbitrariness of weighing the welfare of future generations versus the welfare of the current generation; and (iv) the inequity of imposing higher economic costs on today’s generation to primarily benefit future generations who are expected to be far better off; and (v) that none of these policies, either individually or collectively, will have any measurable impact on world climate, given the increased emissions in developing countries whose primary focus is on economic growth and improved well-being for their citizens. The paper concludes by recommending that, as demand for energy increases over time, the most advantageous policies will focus on stimulating additional research to develop low-cost, reliable, and emissionsfree energy resources. Doing so will provide greater long-term benefits than the current practice of skewing energy policy decisions to favor specific types of technologies and adopting policies that raise costs today. By raising energy costs and, thus, the costs of all goods and services, these policies impose real economic damages today while having no measurable impact on world climate